A study to know clinical characteristics and outcome of obstetrics patients requiring ICU admission - Garg, Pratibha; Tripathi, Urmila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy poses unique consideration for critical care and it is imperative that obstetrician and other members of health care team have a working knowledge of these factors because these are women are usually young and in good health, their prognosis should be better than that of many other patients admitted to an intensive care. Methods: The present study was conducted in the Department of Obstetrics and Gynaecology, Gaja Raja Medical College and associate Kamla raja Hospital, Gwalior in the ICU from Oct. 14 to Oct. 15. Results: 678 obstetric women were admitted into the ICU of Kamla Raja Hospital, over a period of 1 year study period. Maximum number of patients belong to age group 21-25 years (54.8%), 398 (58.7%) patients were uneducated, 343 (50.59%) came directly to Kamla Raja Hospital. 362 (53.39%) belongs to urban area. The mean length of stay in ICU was 3 days. Maximum number of patients were postpartum 580 (85.55%). According to mode of delivery maximum number of patients 348 (51.33%) underwent LSCS. Most common obstetric indication for admission in ICU was hypertensive disorder of pregnancy 472 (69.61%). Most common medical indication was severe anaemia 128 (18.87%). Various type intervention like pulse oxymetry, O2 inhalation, BT, nebulisation and ventilation were done in ICU according to patients need. 43 maternal death happened during the study period with most common cause was cardiorespiratory arrest 9 (1.32%) and pulmonary edema 8 (1.17%). Conclusions: Establishment of a dedicated obstetric ICU at tertiary care centre with knowledge familiarity, experience and expertise of an obstetrician and a special team would be best place to monitor and treat the critically ill obstetric patients which will reduce the maternal morbidity and mortality.